THE ATTRIBUTION ON STUDENTS’ SPEAKING ANXIETY IN EFL CLASSROOM - Syamsin Nurussalam Abdul Mahpudilah (Journal of English and Education, 2016)
Anxiety has been considered as negative influence in learning a language. In speaking, it is also reported to be debilitating for the students’ performance and achievement. This study examined the attribution of students’ speaking anxiety in EFL speaking class. The attribution itself refers to explanation or reason someone made toward an event or experience happened to them in the past. Descriptive qualitative case study design were employed. The participants were twenty nine students of EFL program in a University in Bandung, West Java. The participants were categorized based on their anxiety level by using Foreign Language Classroom Anxiety Scale (FLCAS). Mostly, the students were in mildly anxious level. Only nine anxious students were found and became the focus of the research. They were administered an open-ended questionnaire contained 3 item questions. The result of the study was shown that anxious students of EFL speaking class proposed lack of confidence as major attribution. The co-related attribution were also commonly mentioned: grammar mastery; and negative encouragement from friends; were also related to lack of confidence, which all of them tend to blame for the students themselves. It is suggested for the student to do a self-assessing activity which help them know their own skill, so they can have more confidence. It is also suggested for the lecturer to build good connection with the students in order to help them maintain their anxieties.